Tirzepatide Immunogenicity on Pharmacokinetics, Efficacy, and Safety: Analysis of Data From Phase 3 Studies - Mullins, Garrett R; Hodsdon, Michael E; Li, Ying Grace; Anglin, Greg; Urva, Shweta; Schneck, Karen; Bardos, Jennifer N; Martins, Ricardo Fonseca; Brown, Katelyn; Calderon, Boris (The journal of clinical endocrinology and metabolism, 2024)
Abstract Context Antidrug antibodies (ADA) can potentially affect drug pharmacokinetics, safety, and efficacy. Objective This work aimed to evaluate treatment-emergent (TE) ADA in tirzepatide (TZP)-treated participants across 7 phase 3 trials and their potential effect on pharmacokinetics, efficacy, and safety. Methods ADA were assessed at baseline and throughout the study until end point, defined as week 40 (SURPASS-1, -2, and -5) or week 52 (SURPASS-3, -4, Japan-Mono, and Japan-Combo). Samples for ADA characterization were collected at SURPASS trial sites. Participants included ADA-evaluable TZP-treated patients with type 2 diabetes (N = 5025). Interventions included TZP 5, 10, or 15 mg. ADA were detected and characterized for their ability to cross-react with native glucose-dependent insulinotropic polypeptide (nGIP) and glucagon-like peptide-1 (nGLP-1), neutralize tirzepatide activity on GIP and GLP-1 receptors, and neutralize nGIP and nGLP-1. Results TE ADA developed in 51.1% of tirzepatide-treated patients. Proportions were similar across dose groups. Maximum ADA titers ranged from 1:20 to 1: 81 920 among TE ADA+ patients. Neutralizing antibodies (NAb) against TZP activity on GIP and GLP-1 receptors were observed in 1.9% and 2.1% of patients, respectively. Less than 1.0% of patients had cross-reactive NAb against nGIP or nGLP-1. TE ADA status, ADA titer, and NAb status had no effect on the pharmacokinetics or efficacy of TZP. More TE ADA+ patients experienced hypersensitivity reactions or injection site reactions than TE ADA– patients. The majority of hypersensitivity and injection site reactions were nonserious and nonsevere, and most events occurred and/or resolved irrespective of TE ADA status or titer. Conclusion Immunogenicity did not affect TZP pharmacokinetics or efficacy. The majority of hypersensitivity or injection site reactions experienced by TE ADA+ patients were mild to moderate in severity.